Penerapan Fabric Manipulation Teknik Spiral Dan Draping Pada Busana Pesta Malam Gala Dengan Hiasan Payet. - Arina Haq; Adinda Aisyah Fattahul Qullub (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Fabric manipulation is a technique to decorate the fabric to produce the impression arising on the fabric, fabric manipulation used in this study spiral techniques and draping techniques. Problems in making research related to “how to apply fabric manipulation spiral and draping techniques on evening evening party dress with sequin decoration?” , this study aims to determine the process of applying fabric manipulation spiral and draping techniques on gala evening party dress with sequin decoration. Applying Fabric manipulation with spiral and draping techniques on gala evening party dresses that look luxurious is getting more luxurious. Gala evening party dress with additional sequin decoration that makes it look sparkling. This study uses data collection with observation, literature, and documentation while the data analysis used is qualitative. The process of making a gala evening party dress consists of the top of the party dress, mermaid skirt and tail, this begins by going through several stages, namely: determining the design, preparing tools and materials, taking measurements, making basic patterns and breaking patterns, cutting materials, the process of making fabric manipulation with spiral techniques and draping techniques, sewing party clothes. Suggestions before making fabric manipulation spiral techniques and draping techniques need to be tested to determine the amount of material to be used, the selection of materials also needs to be considered such as light colors and preferably plain fabrics.